Efektivitas Perkembangan Implementasi Trias Politica dalam Kinerja Lembaga Tinggi Negara - Rohmatul Jannah; Keisya Oktavia Afida Denna; Theo Galih Prayudha; Gilang Mafliano Rachmatshah; Tedy Irawan; Kuswan Hadji (Perspektif Administrasi Publik dan hukum, 2024)
This research aims to analyze the effectiveness of developments in the implementation of Trias Politica principles in the performance of high state institutions in Indonesia. Trias Politica, which refers to the separation of powers into executive, legislative and judiciary, is an important foundation in a democratic government system. Through a qualitative approach, this research evaluates how the division of power has transformed since the implementation of political reform in Indonesia, as well as its impact on the performance of state institutions in carrying out their duties and functions. The research results show that although there have been significant developments in the implementation of Trias Politica, several challenges such as overlapping authority, lack of synergy between institutions, and political influence remain obstacles. However, the application of the principle of separation of powers has generally increased accountability, transparency and efficiency in the performance of high state institutions. This research recommends strengthening coordination between institutions and more stringent legal reforms to improve the performance of state institutions as a whole.